Melanocytic Nevus in the External Auditory Canal with Keratin Accumulation - Jeong, Junhui; Lee, Kyuin; Choi, Hyun Seung (Case Reports in Otolaryngology, 2021)
Nevus is a benign melanocytic neoplasm and the most common type of skin tumor. It may occur anywhere on the skin, but it is rare in the external auditory canal (EAC). We present a case of melanocytic nevus in the EAC with keratin accumulation. In microscopic surgery, the mass was excised completely, and the wax and keratin material medial portion of the EAC behind the mass was removed. In this patient, a melanocytic nevus in the EAC caused symptoms of hearing loss and wax and keratin buildup. For melanocytic nevus in the EAC, excision and pathologic confirmation should be performed if there are symptoms or when malignant transformation is suspected.